2015
DOI: 10.1007/s10902-015-9653-5
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Meaning in Life Among Chinese University Students

Abstract: The current studies were designed to explore the structure of sources of meaning in life among Chinese university students. In Study 1, we content-analyzed 171 students' answers to the question of what made their lives meaningful and derived 74 frequently mentioned ideas. Then, we composed a questionnaire based on these ideas and administered it to another sample of 523 university students in Study 2. Seven underlying dimensions were identified through exploratory factor analysis: Self-development (i.e., to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
(44 reference statements)
3
22
0
2
Order By: Relevance
“…The results of this study suggest that religious activities (measured by self-identified religious affiliation, religious attendance, or practice) are significantly associated with a higher level of happiness among respondents in China, despite an atheistic social environment and regulations. These findings are generally consistent with the findings in Western societies where religion is a social norm, as well as in peer studies using Chinese national representative samples (Chen and Williams 2016;He et al 2016;Lu and Zhang 2016;Zhang et al 2016;Lu and Gao 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study suggest that religious activities (measured by self-identified religious affiliation, religious attendance, or practice) are significantly associated with a higher level of happiness among respondents in China, despite an atheistic social environment and regulations. These findings are generally consistent with the findings in Western societies where religion is a social norm, as well as in peer studies using Chinese national representative samples (Chen and Williams 2016;He et al 2016;Lu and Zhang 2016;Zhang et al 2016;Lu and Gao 2017).…”
Section: Discussionsupporting
confidence: 90%
“…However, China has a long history of religion, and there has been a religious awakening in China during the past decades (Chau 2010;Liu et al 2011;Wei and Liu 2013;Ying et al 2017). Existing studies on the relationship between religion and happiness in mainland China have presented some mixed results (Deng et al 2019;Liu and Koenig 2013;Chen and Williams 2016;He et al 2016;Lu and Zhang 2016;Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research has supported the reliability and validity of this scale [33, 34]. For the purpose of this study, the Meaning in Life Questionnaire was translated into Chinese and back-translated from Chinese to English to ensure accurate translation; the translation was found to have good reliability and validity [35]. In the current study, estimated internal consistencies were α = 0.74 (search) and α = 0.81 (presence).…”
Section: Methodsmentioning
confidence: 76%
“…Objektivitas meaning of life pada siswa dengan nilai-nilai kawruh jiwa yang didasari pada nilai-nilai kehidupan kawruh jiwa dilandasi oleh penelitian-penelitian yang telah menunjukkan adanya objektivitas budaya sebagai unsur penting pada meaning of life individu. Penelitian Zhang (2016) memaparkan adanya unsur budaya dalam meaning of life remaja di China. Hasil senada juga disampaikan Steger et al (2008) yang memaparkan adanya unsur budaya dalam meaning of life individu di Jepang.…”
Section: Simpulanunclassified